The influence of elastomeric yarn upon shape memory alloy wire´s behaviour under different temperature gradients - Cruz, Juliana (2012)
This paper presents the research undertaken at the University of Minho aiming to study the influence of elastomeric yarns upon Shape Memory Alloy wires behaviour, in order to produce dynamic structures as a support to answer specific situations and applications. Several samples were produced using flexinol® NiTi wires in combination with elastomeric yarns, varying the numbers of yarns (1, 2 and 4) and diameters (285, 420 and 620 dtex) in the samples. The Tensile tests were carried out being based to NP EN ISO 2062:1993 standards, using a H100KS Hounsfield Universal Testing Instrument. The results showed that force taken by the group can be increased by increasing the number of elastomeric yarns, or by increasing the linear density of the elastomeric yarns. Also, we concluded that an increase in temperature gradient, caused changes in the settings 1 to 4 when used 285 dtex yarn, increasing the force supported.